Effect of Mg/Mo Ratio in Stoichiometric Sr2MgMoO6-δ (SMM)Redox-Stable Anode. (30th May 2017) - Thomas, Tony; Qi, He; Liu, Xingbo; Zondlo, John W.; Sabolsky, Edward M.; Hart, Richard
Abstract : Stoichiometric SMM has a conductivity of 50 S/cm in a reducing atmosphere but with consecutive redox cycling, the conductivity decreases. Effort has been made to understand the reason for the drop in electrical conductivity with increasing redox cycling. It has been found that the Mo concentration may change with time at 800 o C, accounting for the drop in conductivity. This work investigated the electrical performance of the SMM composition as a function of Mg/Mo ratio and level of excess Mo. In addition, the work investigated the thermal and electrical stability as function of operation and thermal cycling. It was found that at a Mg/Mo ratio of 0.9/1.1, the material achieved both thermal and electrical redox stability. From redox dilatometry, it was found that Sr2 Mg0.9 Mo1.1 O6-δ experienced a reversible volumetric reduction of 0.017% and had a reversible electrical conductivity of 17.5 S/cm in a reducing atmosphere.